Strategi Pengembangan UMKM Melalui Pelatihan Wirausaha Kuliner Makanan - Raissa Meidiva Yashinta (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, yet they still face various structural challenges such as limited capital, market access, and low managerial capacity. One strategy considered effective in supporting MSME development is entrepreneurship training, particularly in the culinary sector, which holds high growth potential. This study aims to analyze the influence of culinary entrepreneurship training on the income and sustainability of MSMEs. The research method used is qualitative with a literature review approach, examining various scholarly sources such as journals, books, and official reports. The results show that entrepreneurship training significantly contributes to strengthening the technical, managerial, and product innovation capabilities of MSME actors, ultimately impacting income growth and business resilience. In conclusion, culinary entrepreneurship training is a key factor in fostering independent, competitive, and sustainable MSMEs and should be strategically integrated into empowerment programs at both local and national levels. Keyword: MSMEs, entrepreneurship training, culinary, literature review,